On Sums of Strictly Narrow Operators Acting from a Riesz Space to a Banach Space - Oleksandr Maslyuchenko; Mikhail Popov (Journal of Function Spaces)
We prove that if E is a Dedekind complete atomless Riesz space and X is a Banach space, then the sum of two laterally continuous orthogonally additive operators from E to X, one of which is strictly narrow and the other one is hereditarily strictly narrow with finite variation (in particular, has finite rank), is strictly narrow. Similar results were previously obtained for narrow operators by different authors; however, no theorem of the kind was known for strictly narrow operators.